Utilizations of anti-dumping and countervailing duty investigations in the FTA era - Cheung, Jaeho (The Korea Institute of Public Finance SeoulKR, 2013)
Confirms the increasing significance of trade remedy measures (AD/CVD) as the institutional foundation to allow Korean companies to compete in a fairer trade environment. Examines the current status of AD/CVD measures in Korea while exploring the role of the KTC in charge of Ad/CVD investigations. Addresses the content and issues related to the revision of the WTO anti-dumping and SCM agreements and the position of the Korean government in the participation of these negotiations. Analyses the operation of these measures in other countries and compares them with those of Korea. Draws policy implications for Korea bases on the preceding discussions. Summaries the discussions and draws a conclusion.